Rintisan Museum Mini Tanaman Obat Endemik Suku Anak Dalam sebagai Upaya Pelestarian Etnobotani - Yuliawati, Yuliawati; Maharini, Indri; Efendi, Muhammad Rifqi; Ihsan, Mahya; Lestari, Uce; Astuti, Novita Tri (Jurnal Abdimas Kesehatan (JAK), 2025)
Suku Anak Dalam, also known as SAD in Jambi Province, has undergone modernization in terms of attire and medical practices. In the past, if there was a disease, traditional medicine was the main choice and if it could not be treated, then treatment was done through special rituals. Nowadays, the SAD community prefers choosing nearby health services such public health center or hospital. The preservation of endemic medicinal plants as a local medical tradition must be strengthened, as this will aid traditional medicine research. This community service aims to preserve endemic medicinal plants of the Suku Anak Dalam by creating a mini museum consisting of specimens and books of medicinal plants as well as endemic medicinal plant gardens. The project began with collecting of SAD endemic medicinal plant specimens, which will be used to fill the interior of the upcoming mini-museum. A total of 31 medicinal plant specimens were obtained from the forest near the Anak Dalam Tribe healer residence. Considering the number of endemic medicinal plants acquired remain limited, the team continues to collect additional specimens. The team believes that numerous endemic medicinal plants have yet to be explored. This collection aims to represent the medicinal plants of the Suku Anak Dalam (SAD).